A workplace email-linked website intervention for modifying cancer-related dietary and lifestyle risk factors: rationale, design and baseline findings - Ang, Yee Kwang; Kandiah, Mirnalini; Mohd Shariff, Zalilah (Nutrition Society of Malaysia, 2013)
INTRODUCTION:The use of email and website as channels for workplace health information delivery is not fully explored. This study aims to describe the rationale, design, and baseline findings of an email-linked website intervention to improve modifiable cancer risk factors. METHODS:Employees of a Malaysian public university were recruited by systematic random sampling and randomised into an intervention (n = 174) or control group (n = 165). A website was developed for the intervention and educational modules were uploaded onto the website. The intervention group received ten consecutive weekly emails with hypertext links to the website for downloading the modules and two individual phone calls as motivational support whilst the control group received none. Diet, lifestyle, anthropometric measurements, psychosocial factors and stages of change related to dietary fat, fruit and vegetable intake, and physical activity were assessed. RESULTS:Participants were predominantly female and in non-academic positions. Obesity was prevalent in 15% and 37% were at risk of co-morbidities. Mean intake of fats was 31%, fruit was -1 serving/day and vegetable was < 1 serving/day. Less than 20% smoked and drank alcohol and about 40% were physically inactive. The majority of the participants fell into the Preparation stage for decreasing fat intake, eating more fruit and vegetables, and increasing physical activity. Self-efficacy and perceived benefits were lowest among participants in the Precontemplation/Contemplation stage compared to the Preparation and Action/Maintenance stages. CONCLUSION:Baseline data show that dietary and lifestyle practices among the employees did not meet the international guidelines for cancer prevention. Hence the findings warrant the intervention planned.